First Grade Elementary School Students’ Reflective Thinking Skills in Thematic Learning. - Rahayu Setyowati; Suprapti (JENIUS (Journal of Education Policy and Elementary Education Issues), 2022)
This study elucidates the reflective thinking ability as one of the higher-order thinking skills (HOTS) in thematic learning of grade I students. It also identifies factors affecting students’ reflective thinking ability at MI Al-Islam Kartasura. This study is nested in a qualitative method with a descriptive case study. Involving students of class IA and a class teacher, data collection was carried out using non-test techniques in the form of observation, interviews, and documentation. The results indicated that students could answer the "why" and "how" questions given by the teacher with various answers. They showed their interest or feelings as well as expressed their opinion on pictures or objects about pictures presented by the teacher. They also enjoy having a simple game. Factors supporting the reflective thinking ability as a part of HOTS  are the availability of media, infrastructure, and learning resources, good delivery of lessons by teachers, and curiosity. The obstacle is that its execution takes a long time and demands a high level of focus in student learning.